2020
DOI: 10.1073/pnas.2013432117
|View full text |Cite
|
Sign up to set email alerts
|

Goal-directed and stimulus-driven selection of internal representations

Abstract: Adaptive behavior relies on the selection of relevant sensory information from both the external environment and internal memory representations. In understanding external selection, a classic distinction is made between voluntary (goal-directed) and involuntary (stimulus-driven) guidance of attention. We have developed a task—the anti-retrocue task—to separate and examine voluntary and involuntary guidance of attention to internal representations in visual working memory. We show that both voluntary and invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
169
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(196 citation statements)
references
References 50 publications
24
169
2
1
Order By: Relevance
“…Most critically, the gaze bias was absent during the last 500 ms before online saccade detection (i.e., the initial fixation interval) in the subsequent trial (n + 1), excluding the possibility that the observed trial-to-trial amplitude changes simply reflect a lingering attentional bias. The absence of a gaze bias during the end of the fixation interval cannot be explained by the presence of the fixation cross alone: previous work, in which participants memorized a task-relevant stimulus, found a gaze bias even in the presence of a fixation cross throughout the trial 25 , 26 . Moreover, the gaze bias did not reappear after the primary saccade in trial n + 1.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Most critically, the gaze bias was absent during the last 500 ms before online saccade detection (i.e., the initial fixation interval) in the subsequent trial (n + 1), excluding the possibility that the observed trial-to-trial amplitude changes simply reflect a lingering attentional bias. The absence of a gaze bias during the end of the fixation interval cannot be explained by the presence of the fixation cross alone: previous work, in which participants memorized a task-relevant stimulus, found a gaze bias even in the presence of a fixation cross throughout the trial 25 , 26 . Moreover, the gaze bias did not reappear after the primary saccade in trial n + 1.…”
Section: Resultsmentioning
confidence: 88%
“…Second, amplitude changes could reflect a lingering attentional bias, in the sense that saccade targeting is not only determined by the signal from the peripheral saccade target but also by lingering activity from the previous trial. Such an attentional bias might arise from memorizing the task-relevant stimulus and its location for the subsequent response and should also be apparent in a consistent bias in gaze position over the course of one trial 25 , 26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that to test the effect of gate switching on prioritization, we excluded trials from the temporal dynamic analysis where the same stimulus was repeated from the previous trial. This exclusion allowed us to control for impact of perceptual switches that could have elicited an involuntary stimulus-driven enhancement of memory representations that match the probed category stimulus (e.g., [28, 92]). Therefore, we restricted analysis to output repeat trials involving a perceptual change (e.g., from “X” to “O”), while output switch trials also included a category change (e.g., from “X” to “%”).…”
Section: Methodsmentioning
confidence: 99%
“…Neurons expressing dopamine D1 and D2-receptor in the PFC is different but both neurons project striatum [ 13 , 14 ]. Corticostriatal circuit is important for the goal-directed action [ 15 ], which contribute attention [ 16 ]. In this study we showed that blockade of dopamine D2-receptor in the PFC induced c-Fos expression in the DMS and DLS.…”
Section: Main Textmentioning
confidence: 99%